2001
DOI: 10.1089/107999001750133195
|View full text |Cite
|
Sign up to set email alerts
|

Immunoglobulin Subclasses in Patients with Neutralizing and Nonneutralizing Antibodies Against IFN-β1b

Abstract: Treatment of multiple sclerosis (MS) with interferon-beta1b (IFN-beta1b) induces the production of antibodies in some patients. A proportion of these antibodies can reduce the biologic activity of IFN-beta, and they are, therefore, referred to as neutralizing antibodies (NAB). The remaining antibodies do not interfere with the biologic activity of IFN-beta and are referred to as nonneutralizing antibodies (NNAB) in this paper. Immunoglobulin (Ig) subtyping of these antibodies was carried out, and Ig subclass p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
28
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 20 publications
3
28
0
Order By: Relevance
“…We have shown the presence of both IgG1 and IgG4-ADA contributing to the IFNβ-specific ADA profile. Earlier studies have shown a predominance of IgG4-ADA against IFNβ1a preparations [12] and, IgG2 and IgG4-ADA to IFNβ1b preparation [11]. These observations are similar to the immunogenic responses against glatiramer acetate (GA) treatment in RRMS which has shown predominance of IgG4-ADA [17,18].…”
Section: Discussionsupporting
confidence: 69%
“…We have shown the presence of both IgG1 and IgG4-ADA contributing to the IFNβ-specific ADA profile. Earlier studies have shown a predominance of IgG4-ADA against IFNβ1a preparations [12] and, IgG2 and IgG4-ADA to IFNβ1b preparation [11]. These observations are similar to the immunogenic responses against glatiramer acetate (GA) treatment in RRMS which has shown predominance of IgG4-ADA [17,18].…”
Section: Discussionsupporting
confidence: 69%
“…9 The neutralizing antibody in multiple sclerosis (MS) patients is enriched for the IgG4 isotype, and neutralizing IgG antibodies as a whole are found at higher titers than in patients with the non-neutralizing antibody. 10 The development of IgG class antibodies has been shown to correlate with the development of an antigen-specific response by CD4 þ T cells. [11][12][13][14] To investigate the basis for the development of NAbs, the sequence of human IFN-b-1b was examined for the presence of CD4 þ T-cell epitope regions using a previously established systematic in vitro method.…”
Section: Introductionmentioning
confidence: 99%
“…BAb detection with RIPA technique is simple, inexpensive, and easy to standardize in different routine laboratories, but with the limit that 125 I IFN-should be used within 7 days to avoid radiolysis or proteolysis [110]. It should be reminded that RIPA measures antibodies of IgG class [95,102] without subtype distinction, while antibodies that reduce the biological activity of IFNare primarily of IgG2 and IgG4 isotypes [113]. RIPA results correlate significantly more with changes in lesion burden detected by MRI than NAb titres, but no NAb-positive sample is negative in RIPA [105].…”
Section: Methodological Approaches To Quantify Anti-ifn-antibodiesmentioning
confidence: 99%